2004
DOI: 10.1345/aph.1d543
|View full text |Cite
|
Sign up to set email alerts
|

Treating Functional Impairment of Autism with Selective Serotonin-Reuptake Inhibitors

Abstract: Benefits with SSRIs in treating functional impairments in autism have been observed. Response to therapy and adverse effects are individualized. Current evidence does not support selection of one SSRI over another for any impairment associated with autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2007
2007
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 19 publications
0
29
0
1
Order By: Relevance
“…Although Mulder and colleagues (2005) did find an association between rigid and compulsive behavior in autism and the intron2 VNTR (variable number tandem repeat) of the serotonin transporter gene, in general, results have been inconsistent. Treatment studies provide further evidence that serotonin is involved in the severity of repetitive behaviors, as many studies have shown that SSRIs are effective in reducing autistic symptoms (DeLong et al 1998;Moore et al 2004;Sugie et al 2005). Additionally, Coon et al (2005) found a possible association between a variant of tryptophan hydroxylase (TPH2), a rate-limiting enzyme involved in controlling serotonin synthesis, and higher scores on the ADI-R repetitive behaviors domain.…”
Section: Discussionmentioning
confidence: 99%
“…Although Mulder and colleagues (2005) did find an association between rigid and compulsive behavior in autism and the intron2 VNTR (variable number tandem repeat) of the serotonin transporter gene, in general, results have been inconsistent. Treatment studies provide further evidence that serotonin is involved in the severity of repetitive behaviors, as many studies have shown that SSRIs are effective in reducing autistic symptoms (DeLong et al 1998;Moore et al 2004;Sugie et al 2005). Additionally, Coon et al (2005) found a possible association between a variant of tryptophan hydroxylase (TPH2), a rate-limiting enzyme involved in controlling serotonin synthesis, and higher scores on the ADI-R repetitive behaviors domain.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin reuptake inhibitor medications, which interfere with activity of SLC6A4, are effective in treating specific aspects of autistic symptoms. 12 Multiple SLC6A4 polymorphisms have therefore been studied and found to be associated with autism [13][14][15] ; of these, 5-HTTLPR has attracted the most attention. A primarily biallelic polymorphism, 5-HTTLPR is located in the SLC6A4 promoter region and has short (S) and long (L) alleles that differ in size by 44 nucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…154 The evidence regarding the efficacy of psychopharmacologic interventions in patients with ASDs has been de- 157 and fluvoxamine 158,159 in the treatment of repetitive and other maladaptive behaviors in patients with ASDs, and open-label trials of these and other SSRIs have shown improvements in target symptoms, including repetitive behaviors, irritability, depressive symptoms, tantrums, anxiety, aggression, difficulty with transitions, and aspects of social interaction and language. [157][158][159][160][161] Potential adverse effects of SSRIs include but are not limited to nausea, drowsiness, sexual dysfunction, constipation, abdominal discomfort, fatigue, headache, dizziness, dry mouth, agitation, behavioral activation, hypomania or mania, apathy, suicidal ideation, and alteration of sleep.…”
Section: Psychopharmacologymentioning
confidence: 99%